Role of efflux pumps inhibitor in decreasing antibiotic resistance of Klebsiella pneumoniae in a tertiary hospital in North India - Filgona, Joel; Banerjee, Tuhina; Anupurba, Shampa (The Journal of Infection in Developing Countries, 2015)
Introduction: The contribution of efflux systems to drug resistance in Enterobacteriaceae is becoming increasingly appreciated. This study phenotypically analyzed the role of efflux mechanisms in resistance to ertapenem, doripenem, and tigecycline among clinical isolates of carbapenem-resistant Klebsiella pneumoniae (CRKP). Methodology: Multidrug-resistant and carbapenem non-susceptible K. pneumoniae isolates were determined by disk diffusion test. Further susceptibility of these isolates to carbapenems, ceftriaxone, cefoperazone, ceftazidime, tigecycline, and colistin was determined by agar dilution assay, and CRKP was identified. While modified Hodge test was used to confirm carbapenemase production, the contribution of efflux mechanisms was determined by a minimum inhibitory concentration (MIC) reduction assay, and typing was done by enterobacterial repetitive intergenic consensus (ERIC) polymerase chain reaction (PCR). Results: Of the 238 isolates of K. pneumoniae, 174 were multidrug resistant and 74 were CRKP. Forty of the CRKP were positive for carbapenemase production, while 43, 11, and 2 of the CRKP isolates had elevated MIC of ≥ 32 µg/mL for ertapenem, doripenem, and tigecycline, respectively. Twofold or higher MIC reduction to ertapenem, doripenem, and tigecycline was observed in 6, 28, and 27 isolates, respectively; however, non-susceptibility to ertapenem, doripenem and tigecycline was abolished in 2, 11, and 18 K. pneumoniae isolates, respectively. Nine clones of CRKP widely distributed within the hospital were obtained from ERIC PCR. Conclusions: Although colistin retained better activity against CRKP, efflux pumps contributed to increased MIC in ertapenem, doripenem, and tigecycline. Therefore, efflux systems are important aspects that should be explored in the fight against multidrug-resistant bacteria.